Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5194/amt-7-3565-2014
|View full text |Cite
|
Sign up to set email alerts
|

Instrument concept of the imaging Fourier transform spectrometer GLORIA

Abstract: Abstract. The Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA) is an imaging limb emission sounder operating in the thermal infrared region. It is designed to provide measurements of the upper troposphere/lower stratosphere with high spatial and high spectral resolution. The instrument consists of an imaging Fourier transform spectrometer integrated into a gimbal. The assembly can be mounted in the belly pod of the German High Altitude and Long Range research aircraft (HALO) and in instr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 35 publications
2
89
0
Order By: Relevance
“…From the intensities of the measured spectrally resolved radiation, atmospheric parameters like temperature and a variety of trace gases can be retrieved. A detailed description of the GLORIA measurement concept can be found in Friedl-Vallon et al (2014).…”
Section: Measurement Principlementioning
confidence: 99%
“…From the intensities of the measured spectrally resolved radiation, atmospheric parameters like temperature and a variety of trace gases can be retrieved. A detailed description of the GLORIA measurement concept can be found in Friedl-Vallon et al (2014).…”
Section: Measurement Principlementioning
confidence: 99%
“…Airborne observations by MIPAS-STR (e.g., Piesch et al, 1996;Woiwode et al, 2012, and references therein) and CRISTA-NF (e.g., Ungermann et al, 2012) showed that middle infrared observations allow the resolution of narrow vertical structures in trace gas distributions along flight track with high accuracy under cloud-free conditions. The next generation of infrared limb sounders involves imaging detectors, and the airborne prototype instrument GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) successfully demonstrated the capabilities of this new detection technique (Friedl-Vallon et al, 2014;Riese et al, 2014). Here, we use observations by the airborne MIPAS-STR to investigate the synergy with the MARSCHALS mm-wave observations under scenarios characterized by different cloudiness.…”
Section: Infrared Observationsmentioning
confidence: 99%
“…This enables remote sensing observations with high vertical and horizontal resolution to resolve small-scale structures (see Riese et al, 2014). The spectral sampling can be switched between 0.625 and 0.0625 cm −1 at the cost of an increased acquisition time in the case of higher spectral resolution (Friedl-Vallon et al, 2014). The gimbal mount and inertial altitude control system allows GLORIA to maintain a steady pointing on a moving aircraft; it can also be used to point the instrument at a range of azimuth angles with respect to the aircraft, covering about 70 • .…”
Section: Gloria (Aircraft Remote Sensing)mentioning
confidence: 99%